CAUSES OF RETICENCE IN EFL CLASSROOMS: A STUDY OF CHINESE UNIVERSITY STUDENTS - Meihua Liu (Indonesian JELT, 2005)
This paper reports the findings of a studys of students’ reticence in Chinese EFL context. The participants were three teachers and 100 university freshmen from three proficiency levels enrolled in an English Listening & Speaking course. Using journals, observations and interviews as a technique of collecting data, the study revealed that (1) the majority of the participants were active during pair work but only a few volunteered to respond to their teachers or actively engaged in group discussions, (2) advanced-level students tended to be more active than their lower-level counterparts, and (3) multiple variables worked together to result in student reticence in EFL classrooms. The results indicate that more research needs to be done to help students become more active and proficient EFL learners. Keywords: reticence, university students, Chinese EFL context